Fostering Innovation Through Knowledge Management with the Role of Electro Companies Culture in Indonesia - Gromyko Bongso (Enrichment : Journal of Management, 2022)
The purpose of this study is to look for direct and indirect effects of organizational culture, knowledge management on innovation in electro manufacturing companies in Indonesia. This research is a quantitative approach. Data obtained by conducting a survey of 433 employees of electro companies. The analytical method used is Structural Equation Modeling (SEM) analysis with AMOS tools. Model testing is carried out and declared fit. The results of this study indicate that there is a direct influence of organizational culture and knowledge management on innovation in Indonesian electro manufacturing employees. Organizational culture can also have a significant effect on knowledge management. This study also shows the indirect effect of organizational culture on innovation through knowledge management. The novelty of this research is that there has been no research related to organizational culture, knowledge management and innovation, especially in the electrical companies in Indonesia. Further research opportunities are domain keys identified.